2021
DOI: 10.1111/1346-8138.15673
|View full text |Cite
|
Sign up to set email alerts
|

Excellent response to secukinumab in an infant with severe generalized pustular psoriasis

Abstract: Generalized pustular psoriasis (GPP) represents the rarest form of psoriasis, which may be potentially fatal. In the last decade, (likely) pathogenic variants in the IL36RN, CARD14 and AP1S3 genes have been associated with monogenic GPP forms. Despite these advances, the genetic basis of most patients with GPP remains unidentified. Treatment of GPP patients is often difficult, with no consensus about the best available options to date. We report herein an infant with severe GPP in whom the disease started at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…The efficacy of secukinumab in pediatric GPP is more limited, but five studies involving a total of eight patients have reported successful use 3,4 . Six of these eight children had previously failed conventional systemic therapy, five had known IL36RN mutations, three were treated with secukinumab monotherapy, and all eight patients experienced rapid and sustained improvement, without adverse events 1‐5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of secukinumab in pediatric GPP is more limited, but five studies involving a total of eight patients have reported successful use 3,4 . Six of these eight children had previously failed conventional systemic therapy, five had known IL36RN mutations, three were treated with secukinumab monotherapy, and all eight patients experienced rapid and sustained improvement, without adverse events 1‐5 …”
Section: Discussionmentioning
confidence: 99%
“…Generalized pustular psoriasis is a rare and severe form of psoriasis that is characterized by recurrent episodes of diffuse cutaneous erythema covered with pinpoint pustules and generally accompanied by fever, general malaise, and elevated inflammatory markers 1 . GPP without a history of plaque psoriasis has been reported in association with IL36RN mutations 2 . The treatment of pediatric GPP can be challenging as it may be refractory to conventional systemic therapies such as acitretin, cyclosporine, and methotrexate 3 …”
Section: Discussionmentioning
confidence: 99%
“…All the children had defervescence and clearance of non‐acral pustules within 72 h, and all the participants except for the one with ACH achieved an Investigator's Global Assessment (IGA) 0/1 at week 24. Secukinumab was also effective in a 4‐week‐old infant with IL36RN and CARD14 gene mutations 63 …”
Section: Systemic Treatmentsmentioning
confidence: 99%
“…Secukinumab is a fully human immunoglobulin‐Gκ IL‐17A monoclonal antibody and decreases IL36R activation by inhibiting IL‐17A and disturbing the inflammatory loop of GPP. Several cases and case series have described the efficacy and safety of secukinumab 19,57–66 . Our team reviewed the efficacy and adverse events of secukinumab in 20 Chinese pediatric patients with GPP, with the ages ranging from 6 to 12 years and the age of onset ranging from 2 months to 11 years 19 .…”
Section: Systemic Treatmentsmentioning
confidence: 99%
“…Secukinumab has shown good efficacy and safety profile for treating pediatric patients less than one year of age. [ 36 ] There is a lack of data for the use of infliximab in children. Apremilast, a PDE-4 inhibitor, has shown to be useful in moderate to severe plaque psoriasis in a few case series, but larger studies are required to establish its efficacy and safety profile in children.…”
Section: Epidemiologymentioning
confidence: 99%